PENGARUH MODEL INDEX CARD MATCH TERHADAP HASIL BELAJAR IPS KELAS V SDN 38 PONTIANAK - Emawati, Emawati; Sugiyono, Sugiyono; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed was to analyze the influence of Index Card Match model to the Social studies learning output in grade V of State Elementary School 38 North Pontianak. The research method was an experiment, form of Quasi Experimental's non-equivalent group design. The research population of all grade V students of Public Elementary School 38 North Pontianak were counted to 43 students. The withdrawal sample( sampel jenuh ) technique used saturation sampling. The technique used was direct observation and measuring. The data collecting instrument was observation and multiplechoice paper. The data result was the average score of class control post-test was 58,91 and the experiment was 64,75. Based on the counting result t-test was 2,12 > t-table Â 2,02 then Ha is accepted. It shows that there is a difference in students learning output of class control and class experiment. The value of effect size was 0,795 with middle criteria. The conclusion of this research was the influence of Index Card Match model the learning output of social studies class V of Public Elementary school 38 North Pontianak on average.Â Keywords: Index Card Match model, Learning output, Social Studies Learning